PERANCANGAN TALI BAJA ELEVATOR OF PASSENGER KAPASITAS ANGKUT 900 KG (12 ORANG), KECEPATAN 150 M/MENIT DAN KETINGGIAN 26 LANTAI - Cut Fara Nadia (2021)
Wire rope is a vital component in the elevator so that the safety factor of the strength of these components must be taken in its use. Wire rope tends to slip on the surface around the pulley wheel if the traction avaibility that occurs is less than the traction relation. In designing a wire rope based on the carrying capacity and speed of the elevator, it uses technical calculations and standard references on the elevator. Based on the elevator specification, it can be known that the traction relation is 1,472 so that to avoid slippage, the traction avaibility must be greater than the traction relation which can be calculated using the Euller formula by considering the coefficient of friction, the contact angle of the pulley and the shape of the pulley groove. By the elevator of passenger Schindler brand in an apartment building with a capacity of 900 kg, a speed of 150 m/minutes and a height of 26 floors, this research focuses on selecting the appropriate wire rope to ensure safety and comfort of the passenger. The safety factor, the amount of rope sheets and the elastic stretch are the criteria chosen in determining the compatible wire rope for use which is arranged in a matrix by comparing the wire rope 8x19 Seale FC type with a diameter of 8 mm, 10 mm and 12 mm and Flat Belt Rope with dimensions 3x30 mm according to Permenaker No. 6 of 2017.